INDONESIA’S NEW MODEL OF BILATERAL INVESTMENT TREATY: COMPARISON WITH BRAZIL - Resha Roshana Putri (Padjadjaran Journal of International Law, 2019)
AbstractIn the past few years, there has been a surge in lawsuits against the mechanism for resolving international investment disputes through the Investors State Dispute Settlement (ISDS) forum proposed by foreign investors who are host states, including Indonesia. Most of the claims are caused by the policies of the host country which are intended to protect the basic rights of the people such as the right to health, the right to a healthy environment, taxes, as well as the minimum standard of wages for workers. This policy provides a loss for foreign investors and is considered a violation of the Bilateral Investment Treaty (BIT). BIT is often recognized to be detrimental to Indonesia, because it can disrupt the sovereignty of the country, especially when dealing with international disputes with foreign investors. This study uses a comparative juridical approach, comparing the BIT model in Indonesia with Brazil, namely Cooperation and Investment Facilitation Agreement (CIFA). Brazil was chosen because it succeeds to reform its investment regime, specifically on its BITs. The results obtained were that Indonesia had to change several provisions in its BITs, which has been regulated CIFA provisions in Brazil, which is not member of the ICSID Convention.Keywords: BIT, CIFA, Investor State Dispute Settlement. AbstrakBeberapa tahun terakhir, ada lonjakan tuntutan hukum terhadap mekanisme penyelesaian sengketa investasi internasional melalui Investor State Dispute Settlement (ISDS) forum yang diusulkan oleh investor asing yang menjadi host states, termasuk Indonesia. Sebagian besar klaim disebabkan oleh kebijakan negara tuan rumah yang dimaksudkan untuk melindungi hak-hak dasar masyarakatnya seperti hak atas kesehatan, hak atas lingkungan yang sehat, pajak, juga standar minimum upah pekerja. Kebijakan ini memberikan kerugian bagi investor asing dan dianggap sebagai pelanggaran Bilateral Investment Treaty (BIT). BIT seringkali dianggap merugikan bagi Indonesia, karena dapat mengganggu kedaulatan negara, khususnya ketika berhadapan dengan sengketa internasional dengan investor asing. Penelitian ini menggunakan pendekatan yuridis normatif dengan metode perbandingan, yaitu dengan membandingkan model BIT di Indonesia dengan Brazilia, yaitu Cooperation and Investment Facilitation Agreement (CIFA). Brazil dipilih karena merupakan negara yang berhasil melakukan reformasi terhadap rezim investasinya, khususnya pada BIT. Hasil yang diperoleh adalah bahwa Indonesia harus merubah beberapa ketentuan dalam BITs nya, seperti yang terkadung dalam CIFA di Brazil, yang bukan merupakan negara anggota dari Konvensi ICSID. Kata Kunci: BIT, CIFA, Penyelesaian Sengketa Investor-Negara